2007
DOI: 10.1016/j.ejheart.2007.01.014
|View full text |Cite
|
Sign up to set email alerts
|

NT‐proBNP correlates with right heart haemodynamic parameters and volumes in patients with atrial septal defects

Abstract: Background: To investigate the role of N-terminal pro-BNP (NT-proBNP) for the estimation of right heart failure and pulmonary pressure in patients with atrial septal defects (ASD) before and after percutaneous defect closure. Methods: We performed correlation analysis for NT-proBNP and right ventricular systolic pressure (RVSP) as well as right ventricular enddiastolic and endsystolic volume (RVEDV, RVESV) determined by cardiac magnetic resonance imaging (MRI) before and up to one year following ASD closure. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 32 publications
2
36
0
5
Order By: Relevance
“…In heart disease due to a left-to-right shunt, such as ASDs and VSDs, NT-proBNP levels are high when the Qp/Qs is high, and the fact that this decreases after surgery indicates that congestive HF due to volume overload may result in increased NT-proBNP levels. [41][42][43] Moreover, right ventricular volume overload due to pulmonary regurgitation after surgery for TOF also leads to increased NT-proBNP levels. [44,45] NT-proBNP levels have been reported as a useful marker of HF in patients with single ventricular circulation after Fontan surgery.…”
Section: Review Articlementioning
confidence: 98%
“…In heart disease due to a left-to-right shunt, such as ASDs and VSDs, NT-proBNP levels are high when the Qp/Qs is high, and the fact that this decreases after surgery indicates that congestive HF due to volume overload may result in increased NT-proBNP levels. [41][42][43] Moreover, right ventricular volume overload due to pulmonary regurgitation after surgery for TOF also leads to increased NT-proBNP levels. [44,45] NT-proBNP levels have been reported as a useful marker of HF in patients with single ventricular circulation after Fontan surgery.…”
Section: Review Articlementioning
confidence: 98%
“…[36][37][38] This is not surprising as wall stress modulates BNP gene expression, 39,40 and one of the main determinants of wall stress is end-diastolic volume. 42 We have clinically followed patients for a further 8.3 months and observed that remodeling of RV volumes was associated with clinical worsening. In a similar study by Gan et al, changes in NT-proBNP levels significantly correlated with change in right ventricular volume, the strongest correlation was seen with changes in right ventricular ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, hasta el momento actual no se ha descrito el comportamiento del péptido natriurético en la patología traumática cardíaca, por lo que, al tratarse de pacientes jóvenes y sin cardiopatía previa, podría estar razonablemente justificada su determinación. Sí están descritos casos que correlacionan valores de proBNP con la gravedad del shunt izquierda-derecha, PAP y dilatación de cavidades derechas en pacientes adultos y pediátricos con defectos septal auricular o ventricular no traumáticos 17,18 .…”
Section: Discussionunclassified